2010
DOI: 10.1258/td.2010.090322
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic laparoscopies in rural areas: a different use for the cystoscope

Abstract: Minimally invasive surgeries are gaining popularity even in rural areas. Diagnostic laparoscopies overcome the disadvantages of open surgical procedures and provide useful diagnostic information. We describe a method of carrying out diagnostic laparoscopies using the cystoscope in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Where patients are particularly poor, clever workarounds help make care more affordable or free (eg, accepting payment-in-kind) or more reachable to patients who travel from far away (eg, scheduling clinics around public transportation times to allow for same-day diagnosis and treatment). Where supplies are limited or unavailable, inexpensive local alternatives are fashioned to fill the need gap (eg, sterilised mosquito net for hernia repair, 30–36 a cystoscope for diagnostic laparoscopy, 37–39 gasless laparoscopy 40 ). Given the broad variation in how governments and policymakers have approached these issues over the years, local clinicians steeped in these clinical environments have the best sense of what their patients are experiencing and how they can provide better care.…”
Section: Discussionmentioning
confidence: 99%
“…Where patients are particularly poor, clever workarounds help make care more affordable or free (eg, accepting payment-in-kind) or more reachable to patients who travel from far away (eg, scheduling clinics around public transportation times to allow for same-day diagnosis and treatment). Where supplies are limited or unavailable, inexpensive local alternatives are fashioned to fill the need gap (eg, sterilised mosquito net for hernia repair, 30–36 a cystoscope for diagnostic laparoscopy, 37–39 gasless laparoscopy 40 ). Given the broad variation in how governments and policymakers have approached these issues over the years, local clinicians steeped in these clinical environments have the best sense of what their patients are experiencing and how they can provide better care.…”
Section: Discussionmentioning
confidence: 99%
“…The need for diagnostic laparoscopic surgeries in rural areas brought many innovations. For example the use of Gas Insufflation Less Laparoscopic Surgeries (GILLS) [2] and the use of cystoscope for laparoscopy in rural areas [1] . This would still require the Laparoscopic camera and the light source.…”
Section: Discussionmentioning
confidence: 99%
“…The modern diagnostic facilities like CT scans and MRI are not available there. Survey of the operation registers of many rural hospitals (17 hospitals) belonging to an association of hospitals in North India revealed that Diagnostic laparotomies were a common surgical procedure in rural areas [1] . Despite the high costs and invasive nature Laparotomies were still carried out in rural areas because of the cost effectiveness and convenience.…”
Section: Introductionmentioning
confidence: 99%
“…3 Unfortunately, the cost of equipment for diagnostic laparoscopy is very high and out of reach of most rural healthcare facilities, especially those who do not perform laparoscopic surgical procedures. Although innovative methods such as using a cystoscope for diagnosis have been tried, 4 they are still expensive because of the high costs of the telescope.…”
mentioning
confidence: 99%